Cafe D’Lagoon Development for Managing Effectivity of Sustainability Management : Pengembangan Cafe D’Lagoon Untuk Pengelolaan Efektifitas Manajemen Keberlanjutan - Rafli Raikhan Syah; Alfiandi Imam Mawardi (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Efficient stock management is a critical factor in the operational sustainability of Café D’Lagoon. The manual recording method previously used caused issues such as data errors, information loss, and slow processes. To address this, a Google spreadsheet -based stock management system was implemented as a simple, modern, and affordable solution. The program involved observation, discussion, training, and implementation. Results showed improved operational efficiency, including reduced stock-taking time, fewer recording errors, and better report accessibility. Employees independently adopted the new technology, enhancing stock management accuracy and speed. This implementation demonstrates that simple technology can significantly impact small business efficiency and serves as an inspiration for similar businesses.